An introduction to atmospheric physics - Andrews, David G (Cambridge University Press, 2010)
"A quantitative introduction to the Earth's atmosphere for intermediate-advanced undergraduate and graduate students, with an emphasis on underlying physical principles. This edition has been brought completely up-to-date, and now includes a new chapter on the physics of climate change which builds upon material introduced in earlier chapters, giving the student a broad understanding of some of the physical concepts underlying this most important and topical subject. In contrast to many other books on atmospheric science, the emphasis is on the underlying physics. Atmospheric applications are developed mainly in the problems given at the end of each chapter. The book is an essential resource for all students of atmospheric physics as part of an atmospheric science, meteorology, physics, Earth science, planetary science, or applied mathematics course"